Penerapan Metode Hazops untuk Keselamatan dan Kesehatan Kerja Pada Proses Produksi Rak Dies di CV. Sarana Sejahtera Tehnik - Ikmal Mauladi; Kusnadi Kusnadi (Jurnal Ilmiah Wahana Pendidikan, 2022)
Work safety is a state of avoiding danger while doing work. Work safety is one of the factors that must be done during work, no one in the world wants an accident to occur. Identification of potential hazards and risks in the work area has an important role in reducing the possibility of accidents occurring. The purpose of this study is to measure the potential hazards and the rate of work accidents using the Hazops method. Data collection techniques for this study used observations and interviews. Data collection methods such as direct observation to the work area with the aim of getting the actual data needed in this study. Interviews were conducted directly with the owner of the company. Based on the results of the study, it is known that there is a low, high and extreme risk of harm. From the results of this study obtained several risks with different levels of danger. As for the low hazard risk found in the working process using Grinding, Shearing, and Sprayer tools, for high levels found in the use of Cutting and Welding machines, and for Extreme levels found when using Crane tools.